The Impacts of Pandemic on Food Security and Food Inflation - Karagöz, Ali; Kandemir, Orhan (Turkish Science and Technology Publishing (TURSTEP), 2023)
One of the most important impacts of the Covid 19 pandemic that broke out in China in the last months of 2019 was on the agricultural sector and, consequently, on the food supply. This situation manifested itself in an increase in food insecurity and food prices in countries around the world, and rising food prices highlighted the risk of undernourishment. The study attempted to statistically represent the impact of the pandemic on food security and food price increases in countries around the world. The study first compared the pre-pandemic and pandemic periods in terms of three basic indicators, such as food security, food prices, and undernourishment rates, and examined whether there was a significant difference between the two periods. Within the context of these three indicators, an attempt was then made to determine whether the negative impact of the pandemic was more severe in low-income countries. The results of the analysis showed that food prices, food insecurity, and undernourishment increased during the pandemic and that these impacts were relatively greater in developing countries. Therefore, the financial burden of these negative impacts associated with food supply was greater in developing countries.
Keywords: food inflation; S; undernourishment; Agriculture (General); covid 19 outbreak; Agriculture; food supply assurance; S1-972; 2. Zero hunger; 1. No poverty; 3. Good health